Walt Disney : the triumph of the American imagination - Gabler, Neal. (New York : Alfred A. Knopf, 2006)
A portrait of the private life and public career of Walt Disney ranges from his deprived youth, to his contributions to the art of animation, to his visionary creation of the first synergistic entertainment empire, to his reclusive and lonely private world.
Escape -- Go-getter -- Wonderland -- The mouse -- The cult -- Folly -- Parnassus -- Two wars -- Adrift -- City on a hill -- Slouching toward utopia.
Includes bibliographical references (p. [805]-815) and index.
Keywords: Disney, Walt, -- 1901-1966.; Animators -- United States -- Biography